Micro-Heterogeneity of Flow in a Mouse Model of Chronic Cerebral Hypoperfusion Revealed by Longitudinal Doppler Optical Coherence Tomography and Angiography. Issue 10 (October 2015) - Srinivasan, Vivek J; Yu, Esther; Radhakrishnan, Harsha; Can, Anil; Climov, Mihail; Leahy, Conor; Ayata, Cenk; Eikermann-Haerter, Katharina
Although microvascular dysfunction accompanies cognitive decline in aging, vascular dementia, and Alzheimer's disease, tools to study microvasculature longitudinally in vivo are lacking. Here, we use Doppler optical coherence tomography (OCT) and angiography for noninvasive, longitudinal imaging of mice with chronic cerebral hypoperfusion for up to 1 month. In particular, we optimized the OCT angiography method to selectively image red blood cell (RBC)-perfused capillaries, leading to a novel way of assessing capillary supply heterogeneity in vivo. After bilateral common carotid artery stenosis (BCAS), cortical blood flow measured by Doppler OCT dropped to half of baseline throughout the imaged tissue acutely. Microscopic imaging of the capillary bed with OCT angiography further revealed local heterogeneities in cortical flow supply during hypoperfusion. The number of RBC-perfused capillaries decreased, leading to increased oxygen diffusion distances in the days immediately after BCAS. Linear regression showed that RBC-perfused capillary density declined by 0.3% for a drop in flow of 1 mL/100 g per minute, and decreases in RBC-perfused capillary density as high as 25% were observed. Taken together, these results demonstrate the existence of local supply heterogeneity at the capillary level even at nonischemic global flow levels, and demonstrate a novel imaging method to assess this heterogeneity.